Newly discovered hepatitis C virus minicores circulate in human blood. Issue 1 (12th November 2017) - Eng, Francis J.; El‐Shamy, Ahmed; Doyle, Erin H.; Klepper, Arielle; Muerhoff, A. Scott; Branch, Andrea D.
Abstract : This study provides the first direct evidence that HCV‐expressed non‐classical proteins (minicores) are present in blood during natural infections in addition to the conventional proteins. Abstract : Hepatitis C virus (HCV) is one of the most prevalent causes of chronic blood‐borne infections worldwide. Despite developments of highly effective treatments, most infected individuals are unaware of their infection. Approximately 75% of infections are in low‐ and middle‐income countries; therefore, continuing research in HCV molecular virology and the development of vaccines and affordable diagnostics is required to reduce the global burden. Various intracellular forms of the HCV nucleocapsid (core) protein are produced in cell culture; these comprise the conventional p21 core and the newly discovered shorter isoforms (minicores). Minicores lack the N‐terminus of p21 core. This study was conducted to determine if minicores are secreted in cell culture and more importantly if they circulate in the blood of individuals infected with HCV. We also developed a new monoclonal antibody that detects minicores targeting a C‐terminal region common to p21 core and minicores. Direct evidence of minicores requires western blot analysis to distinguish the detection of p21 core from minicores. However, the sensitivity for western blot detection of HCV proteins from blood is nil without their prior purification/enrichment from blood. Therefore, we developed a purification method based on a heparin/Mn +2 precipitation of apolipoprotein B‐containing lipoproteins because HCV is thought to circulate as a hybrid lipoviral particle. Minicores are secreted in culture when cells are grown in the presence of human serum. The heparin/Mn +2 precipitate from HCV‐infected cell culture supernatants and from the blood of 4 patients with high‐titer genotype‐1 HCV contained minicores. Conclusion : Minicores are major newly discovered HCV proteins that are secreted and circulate in blood during natural infections. Minicore proteins have translational potential as targets in diagnostic assays and in vaccine development. ( Hepatology Communications 2018;2:21–28)